2023
DOI: 10.3389/fpubh.2023.1143751
|View full text |Cite
|
Sign up to set email alerts
|

Ten characteristics of high-quality planetary health education—Results from a qualitative study with educators, students as educators and study deans at medical schools in Germany

Abstract: AimThe climate and ecological crises are considered fundamental threats to human health. Healthcare workers in general and doctors in particular can contribute as change agents in mitigation and adaptation. Planetary health education (PHE) aims to harness this potential. This study explores perspectives among stakeholders involved in PHE at German medical schools on the characteristics of high-quality PHE and compares them to existing PHE frameworks.MethodsIn 2021, we conducted a qualitative interview study wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…This trans-disciplinary field is focused on movement building bolstered by equity and social justice (Rouf and Wainwright, 2020). As a recent emergent discipline, there is still much ongoing debate about which areas of knowledge should be reflected by PH teaching and practice (Simon et al, 2023), with tensions between the medical and environmental disciplines and traditions struggling to prevail in the PH narrative.…”
Section: Pathways In Global Challenges Programmementioning
confidence: 99%
“…This trans-disciplinary field is focused on movement building bolstered by equity and social justice (Rouf and Wainwright, 2020). As a recent emergent discipline, there is still much ongoing debate about which areas of knowledge should be reflected by PH teaching and practice (Simon et al, 2023), with tensions between the medical and environmental disciplines and traditions struggling to prevail in the PH narrative.…”
Section: Pathways In Global Challenges Programmementioning
confidence: 99%
“…It has been shown that health professionals (15) and students (36) are interested in this topic and appreciate an integration in their education. Experiences, ideas and concepts of what planetary health education could look like have already been outlined in studies and models (35,(37)(38)(39)(40).…”
Section: Barriers and Promotion To Climate-specific Health Literacy F...mentioning
confidence: 99%
“…With a dedicated working group for Planetary Health education, the European Planetary Health Hub has aimed to integrate Planetary Health education at all levels, including the future generation of doctors ( 13 ). Several countries, such as Germany, the Netherlands and the United Kingdom, have started to implement Planetary Health courses in their medical school curricula ( 14–16 ). In contrast, in other countries such as Italy, an ecologically sensitive medical education is still lacking, likely limiting physicians’ ability to identify and address climate change-related issues in their clinical practice.…”
Section: Introductionmentioning
confidence: 99%